Dissolved organic matter in the Baltic Sea - Hoikkala, L.; Kortelainen, P.; Soinne, H.; Kuosa, H. (Elsevier, 2015)
Several factors highlight the importance of dissolved organic matter (DOM) in coastal ecosystems such as the Baltic Sea: 1) DOM is the main energy source for heterotrophic bacteria in surface waters, thus contributing to the productivity and trophic state of bodies of water. 2) DOM functions as a nutrient source: in the Baltic Sea, more than one-fourth of the bioavailable nutrients can occur in the dissolved organic form in riverine inputs and in surface water during summer. Thus, DOM also supports primary production, both directly (osmotrophy) and indirectly (via remineralization). 3) Flocculation and subsequent deposition of terrestrial DOM within river estuaries may contribute to production and oxygen consumption in coastal sediments. 4) Chromophoric DOM, which is one of the major absorbers of light entering the Baltic Sea, contributes highly to water color, thus affecting the photosynthetic depth as well as recreational value of the Baltic Sea. Despite its large-scale importance to the Baltic Sea ecosystem, DOM has been of minor interest compared with inorganic nutrient loadings. Information on the concentrations and dynamics of DOM in the Baltic Sea has accumulated since the late 1990s, but it is still sporadic. This review provides a coherent view of the current understanding of DOM dynamics in the Baltic Sea.
Keywords: Baltic Sea; dissolved organic matter; catchment area; biogeochemistry; coastal oceanography; carbon cycling